Rendimento e qualidade industrial de cultivares de trigo submetido à formas de parcelamento da adubação nitrogenada - Rocha, Kassiano Felipe (2014)
Wheat is a winter cereal important for farm in the crop rotation scheme and, primarily to generate income. Nitrogen is the nutrient most required for the culture and is largely responsible for the yield and the composition of industrial breadmaking quality. The management of this nutrient is of paramount importance to provide N in all stages of the plant, being necessary to apply it in installments. The objective of this study was to evaluate the response of split nitrogen fertilization on grain yield and quality of two cultivars of bread wheat. Experiments were conducted in Pato Branco and Curitibanos in randomized block designer in a factorial scheme with three replications. Two bread wheat and 11 forms installment of nitrogen fertilization + control without N. Were used the cultivars BRS Gralha Azul and Quartzo. Was parceled 100 kg N ha-1 following: 100-00-00, 00-100-00, 00-60-40, 00-70-30, 00-80- 20, 60-00-40, 70-00-30, 80-00-20, 50-50-00, 70-30-00, 30-70-00, in double ring, terminal spyke and booting stages, respectively. Were evaluated the morphological characters, yield components, grain yield, Falker chlorophyll index, nitrogen content in plant tissue quality and industrial bakery. In both evaluation sites occurred drought stress on crop development. Grain yield and wheat baking quality were little influenced by split nitrogen fertilization, especially in lanes that showed high levels of organic matter in soil. The BRS Gralha Azul produced a high quality wheat bakery. The use of N in wheat baking quality and yield increases, but not enough to indicate the best way to answer parceling.